PENINGKATAN KINERJA SUMBER DAYA MANUSIA BERBASIS JOB CHARACTERISTIC DAN DUKUNGAN ORGANISASI MELALUI WORK ENGAGEMENT - Isnuryati Isnuryati; Heru Sulistyo (Jurnal Riset Bisnis Indonesia, 2016)
Eemployee performance is also an important factor in providing services to the community andimprove the performance of government, particularly the district of Jepara. This research is purposedto examine how to increase the employee performance based job characteristic and organizationalsupport through work engagement Setda Jepara regency. This study analyzed by partial leastsquare with the respondent to 141 people. The results are Job Characteristic has significant effecton work enggagement but not significant on employee performance, organizations support hassignificant effect on work enggagement but not significant on the employee performance and workenggagement has positive effect on the employee performance.Keywords : Job Characteristic, work enggagement, organizational support dan employeeperformance